Facilitating Narrative Change in Career Construction Counseling - Cardoso, Paulo (2020)
Career Construction Counseling fosters client change by evoking and elaborating innovative moments in client narratives. In this article, we describe four types of dialogues that counselors may use to prompt narrative novelty and foster client change: (a) identify and evaluate the effects of innovative moments, (b) highlight contrasting self-positions, (c) ask about changes achieved, (d) promote a metaperspective on change. Vignettes from a case are used to illustrate how to use IM markers as a heuristic guide for when to engage in these four types of dialogues.